Metformin induced acute kidney injury; a systematic review - Mahnaz Momenzadeh; Bhaskar VKS Lakkakula (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Metformin is the best proven first-line treatment for type 2 diabetes (T2DM), based on both national and international guidelines. The present systematic review is aimed to examine the acute kidney injury (AKI) risk associated with metformin. Methods: A systematic literature search was performed in MEDLINE, PubMed and google scholar, to retrieve the literature related to the metformin use. A bibliographic management software (Endnote X9) was used for managing the literature. The following keywords were used: "Acute renal injury OR ARI", "Acute kidney injury OR AKI"," Metformin", " Type 2 diabetes mellitus OR T2DM", "Diabetic patients", "Renal function", "CKD". Results: About 28 relevant articles were found during the electronic and manual search. Finally, a total of four articles that fulfill the inclusion criteria were used for this systematic literature review. There is no evidence to suggest that metformin increases the incidence of AKI and is associated with an increased survival of 28 days following AKI event. Further, there was no difference in the incidence of AKI in patients who continued metformin after arterial contrast exposure compared with the control group. Conclusion: In summary, there is no evidence that metformin increases the incidence of AKI. More clinical trials are needed in this area, to investigate more evidence so that we can better understand the outcome.